PERBANDINGAN NILAI TAMBAH PEMELIHARAAN LEBAH MADU KELULUT (Trigona itama) DAN LEBAH MADU LOKAL (Apis cerana) DI DESA SUMBER MAKMUR KECAMATAN TAKISUNG KABUPATEN TANAH LAUT - Sulaiman, Sulaiman; Basir, Basir; Helmi, Muhammad (Jurnal Hutan Tropis, 2024)
Honey is one of the leading non-timber forest products (HHBK) in Tanah Laut Regency which was stipulated through the Decree of the Tanah Laut Regent Number 188.45/463-KUM/2013 dated 10 September 2013 concerning Designation as a development area for superior Non-Timber Forest Products (HHBK) in the form of honey. The economic strength resulting from the honey bee cultivation business can be reflected in the value added (value added) of its management. Product added value, output value, production productivity, and also the amount of remuneration to the owner, as well as the factors of production, can be identified by carrying out an added value analysis. The amount of added value can be a reference for whether or not there is added value from the treatment that has been given to the product. The purpose of this research is to analyze the added value of kelulut honey cultivation. Analyzing the amount of added value from local honey cultivation. Comparing the added value of cultivating kelulut honey and local honey bees (A. carena). The object of this research is farmers who cultivate kelulut honey bees and local honey bees with a system of maintenance, production and value added management. The cultivation of kelulut honey bees produces a total output of Rp. 150.000.000 per year. The total added value generated is Rp. 41.217.500, consisting of Rp. 7.540.000, the profit is Rp. 39.859.900, and depreciation of Rp. 3,707,500. Local honey bee cultivation of A. carena produces a total output of Rp. 27.000.000 per year. The total added value generated is Rp. 13.08.000, consisting of Rp. 4.500.000, the profit is Rp. 11.730.000, and depreciation of Rp. 1.220.000. The cultivation of kelulut honey bees generates an added value of Rp. 41.217.500 more than the added value of A. carena local honey bee cultivation with an added value of Rp. 13.008.000.